Are immigrants outbred and unrelated? Testing standard assumptions in a wild metapopulation. Issue 22 (24th September 2021) - Dickel, Lisa; Arcese, Peter; Nietlisbach, Pirmin; Keller, Lukas F.; Jensen, Henrik; Reid, Jane M.
Abstract: Immigration into small recipient populations is expected to alleviate inbreeding and increase genetic variation, and hence facilitate population persistence through genetic and/or evolutionary rescue. Such expectations depend on three standard assumptions: that immigrants are outbred, unrelated to existing natives at arrival, and unrelated to each other. These assumptions are rarely explicitly verified, including in key field systems in evolutionary ecology. Yet, they could be violated due to non‐random or repeated immigration from adjacent small populations. We combined molecular genetic marker data for 150–160 microsatellite loci with comprehensive pedigree data to test the three assumptions for a song sparrow ( Melospiza melodia) population that is a model system for quantifying effects of inbreeding and immigration in the wild. Immigrants were less homozygous than existing natives on average, with mean homozygosity that closely resembled outbred natives. Immigrants can therefore be considered outbred on the focal population scale. Comparisons of homozygosity of real or hypothetical offspring of immigrant‐native, native‐native and immigrant‐immigrant pairings implied that immigrants were typically unrelated to existing natives and to each other. Indeed, immigrants' offspring would be even less homozygous than outbred individuals on the focal population scale. The three standard assumptions of population genetic and evolutionary theory were consequently largely validated. Yet, our analyses revealed some deviations that should be accounted for in future analyses of heterosis and inbreeding depression, implying that the three assumptions should be verified in other systems to probe patterns of non‐random or repeated dispersal and facilitate precise and unbiased estimation of key evolutionary parameters.